FAKTOR YANG MEMPENGARUHI WORD-OF-MOUTH INTENTION PADA PELANGGAN RESTORAN SUSHI TEI DI DKI JAKARTA - MEILAN TOYIBAH HERMANTO; Irma Satya Indriyanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to determine the influence of personal service and functional service on word-of-mouth intention from Sushi Tei’s customer in DKI Jakarta through customer satisfaction as mediating variable. The design that used in this research were descriptive research and causality research, in which variabels were measured with 6 points likert scale. The technique that used in this reseach is non-probability sampling and used 241 respondents who fit the citeria. This research data is processe by using Structural Equation Modeling - Partial Least Square. The results of this calculation show that personal service and functional service through customer satisfaction as mediating variable have an influence on word-of-mouth intention on Sushi Tei’s customers in the DKI Jakarta area. Personal service and functional service have an influence on word-of-mouth intention on Sushi Tei’s customers in the DKI Jakarta Area. Personal service and functional service has effect on word-of-mouth customer satisfaction, enabling companies that focus on their service to better ensure customer satisfaction to get word-of-mouth intention.